PENGEMBANGAN MEDIA POP-UP BOOK 3D (PUBI) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK FASE C SEKOLAH DASAR - Nabhan Labib Musyaffa; Pupun Nuryani; Mubarok Somantri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research addresses the low critical thinking skills of students and the limited learning media available. This study aims to develop a 3D POP-UP BOOK (PUBI) medium to enhance the critical thinking skills of elementary school students in Phase C. The research method employed is Design and Development (D&D), utilizing the ADDIE development model (analysis, design, development, implementation, evaluation). Data collection techniques included questionnaires, observations, and pre-test and post-test administrations. The study used a Likert scale to measure the validation results from experts. The validation results indicate that the 3D POP-UP BOOK (PUBI) medium is highly suitable for use in learning, with an average percentage score of 93% (Very Suitable category) from material experts, 97% (Very Suitable category) from media experts, and 88% (Very Suitable category) from learning experts. Furthermore, there was an improvement in students' critical thinking skills, evidenced by the increased scores from the pre-test to the post-test. The overall average pre-test score was 50, which then increased to an average score of 83. Therefore, it can be concluded that the 3D POP-UP BOOK (PUBI) medium is highly suitable for use in classroom learning and is capable of improving students' critical thinking skills.